2016
DOI: 10.1155/2016/5872423
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacogenetics of Risperidone and Cardiovascular Risk in Children and Adolescents

Abstract: Objective. To identify the frequency of obesity and metabolic complications in child and adolescent users of risperidone. Potential associations with clinical parameters and SNPs of the HTR2C, DRD2, LEP, LEPR, MC4R, and CYP2D6 genes were analyzed. Methods. Samples from 120 risperidone users (8–20 years old) were collected and SNPs were analyzed, alongside assessment of chronological and bone ages, prescribed and weight-adjusted doses, use of other psychotropic drugs, waist circumference, BMI z-scores, blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
11
0
2
Order By: Relevance
“…Secondly, we examined the International HapMap Project database for minor allele frequency more than 0.05 in the Chinese Han in Beijing. Thirdly, significant association has been reported in previous studies; CYP2D6 , ABCB1 , DRD2 , LEP , GHRL , BDNF . Candidate SNPs were identified from all three sources.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…Secondly, we examined the International HapMap Project database for minor allele frequency more than 0.05 in the Chinese Han in Beijing. Thirdly, significant association has been reported in previous studies; CYP2D6 , ABCB1 , DRD2 , LEP , GHRL , BDNF . Candidate SNPs were identified from all three sources.…”
Section: Methodsmentioning
confidence: 83%
“…Considering the association between CYP2D6 gene polymorphisms and metabolic adverse effects, the study by Santos‐Júnior et al . determined the relationship between CYP2D6*10 (c.100 C>T) and metabolic parameters in children and adolescents treated with risperidone. They reported that homozygosity ( C/C and T/T ) was associated with a higher HOMA‐IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a descriptive cross-sectional study. The subjects were children and adolescents who had participated in a previous study that quantified the incidence of obesity, hypertension, insulin resistance, metabolic syndrome, and hyperprolactinemia in children and adolescents to whom risperidone was administered to treat mental and behavioral disorders ( 18 20 ). The inclusion criteria allowed for children and adolescents between the ages of 8 and 18 who were treated in the outpatient psychiatric unit of the Universidade Estadual de Campinas (UNICAMP) Hospital das Clínicas, São Paulo, Brazil between March 2014 and August 2015.…”
Section: Methodsmentioning
confidence: 99%
“…In the article titled “Pharmacogenetics of Risperidone and Cardiovascular Risk in Children and Adolescents” [ 1 ], there was an error in the “Laboratory Evaluation” section, where the selected CYP2D6 SNP is written as rs72552269, and should be corrected to “rs1065852.”…”
mentioning
confidence: 99%